Factors related to intentional non-initiation of bisphosphonate treatment in patients with a high fracture risk in primary care: a qualitative study - Karin M. A. Swart; Myrthe van Vilsteren; Wesley van Hout; Esther Draak; Babette C. van der Zwaard; Henriette E. van der Horst; Jacqueline G. Hugtenburg; Petra J. M. Elders (BMC Family Practice, 2018)
Abstract Background Adherence to osteoporosis treatment is crucial for good treatment effects. However, adherence has been shown to be poor and a substantial part of the patients don’t even initiate treatment. This study aimed to gain insight into the considerations of both osteoporosis patients and general practitioners (GP) concerning intentional non-initiation of bisphosphonate treatment. Methods Osteoporosis patients and GPs were recruited from the SALT Osteoporosis Study and a transmural fracture liaison service, both carried out in the Netherlands. Using questionnaires, we identified non-starters and starters of bisphosphonate treatment. Semi-structured interviews were conducted to gain a detailed overview of all considerations until saturation of the data was reached. Starters were asked to reflect on the considerations that were brought forward by the non-starters. Interviews were open coded and the codes were classified into main themes and subthemes using an inductive approach. Results 16 non-starters, 10 starters, and 13 GPs were interviewed. We identified three main themes: insufficient medical advice, attitudes towards medication use including concerns about side effects, and disease awareness. From patients’ as well as GPs’ perspective, insufficient or ambiguous information from the GP influenced the decision of the non-starters to not start bisphosphonates. In contrast, starters were either properly informed, or they collected information themselves. Patients’ aversion towards medication, fear of side effects, and a low risk perception also contributed to not starting the medication, whereas starters were aware of their fracture risk and were confident of the outcome of the treatment. Concerns about osteoporosis treatment and its side effects were also expressed by several GPs. Some GPs appeared to have a limited understanding of the current osteoporosis guidelines and the indications for treatment. Conclusions Many reasons we found for not starting bisphosphonate treatment were related to the patients or the GPs themselves being insufficiently informed. Attitudes of the GPs were shown to play a role in the decision of patients not to start treatment. Interventions need to be developed that are aimed at GPs, and at education of patients.